PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI CANVA BERBASIS MASALAH PADA TEMA EKOSISTEM KELAS V SD - putri fadhillah; nurjannah (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2023)
This study aims to: (1) develop media using Canva applications in elementary thematic learning, (2) determine the feasibility of developing Canva applications in elementary thematic learning. This research is a type of Research and Development (R&D) research with the ADDIE model which includes five steps, including: analysis, Design, Development, Implementation, Evaluation. The subjects in this study were media expert validators, material experts, education practitioners, namely fourth grade teachers and fourth grade elementary school students. The research instruments used in data collection were questionnaires, observations and documentation. The results of this study indicate that the Canva Application learning media in the Thematic Learning of the Ecosystem Theme for Grade V Elementary School is "Very Eligible" with details of the percentage of eligibility given by media experts in sub theme 1 of 91.6% with the category of "Very Eligible", sub theme media 2 of 91.6% in the "Very Eligible" category, sub theme media 3 by 91,6% in the "Very Eligible" category. Material experts on sub theme media 1 are 96% in the "Very Eligible" category, sub theme 2 is 96% in the "Very Eligible" category, sub theme 3 is 96% in the "Very Eligible" category. For education practitioners in sub theme media 1, 98% in the "Very Eligible" category, 94% in sub theme 2 in the "Very Eligible" category, 96% in sub theme 3 in the "Very Eligible" category.. Therefore, it can be concluded that the Canva Application learning media in the thematic learning of the Ecosystem theme of for grade IV SD SD Negeri 101983 Bangun Rejo is "very feasible" to be used by students during the learning process